Challenges of interagency collaboration in emergency response in Nigeria (2020)
Nigeria as state has been facing a myriad of challenges that have impeded disaster and risk management for years now. This situation is further complicated by the dearth or even lack of a comprehensive institutional framework for emergency response system in the country. The interaction between the agencies involved is one in which there is a usual disconnect instead of a joint decision making approach where power is shared and all agencies take up organizations and the public, but the current approach being employed is rather tailored towards individual coordination rather than a collaborative or cooperative approach. This paper, therefore, examines the challenges of interagency collaboration on emergency response in the country and implications for national risk preparedness and reduction. The study vividly depicts an overview of the Nigerian situation in relation to emergency response. Though challenges crop up as a result of various hindrances that make the agencies work at cross-roads, among which are: financial constraints, inadequate information on coordination process, politics and others. The paper concludes that given the current situation on in-adequate interagency collaboration in emergency response in Nigeria, there is need to embrace interagency collaboration to enhance emergency response to disasters and risks in our societies. It, however, recommends encouragement of coherent policies; learning from the lived experiences of developed countries; coupling disaster risk reduction with other.